So Happy Together: A Review of the Literature on the Determinants of Effectiveness of Purpose-Oriented Networks in Health Care. (June 2023) - Peeters, Robin; Westra, Daan; van Raak, Arno J. A.; Ruwaard, Dirk
While purpose-oriented networks are widely recognized as organizational forms to address wicked problems in health care such as increasing demands and expenditure, the associated literature is fragmented. We therefore reviewed empirical studies to identify the determinants of the effectiveness of these networks. Our search yielded 3, 657 unique articles, of which 19 met our eligibility criteria. After backward snowballing and expert consultation, 33 articles were included. Results reveal no less than 283 determinants of effective health care networks. The majority of these determinants are processual and involving professionals from the operational level is particularly salient. In addition, most studies relate determinants to process outcomes (e.g., improved collaboration or sustainability of the network) and only a few to members' perception of whether the network attains its goals. We urge future research to adopt configurational approaches to identify which sets of determinants are associated with networks' ability to attain their goal of addressing wicked problems.